2020
DOI: 10.1038/s41598-020-59295-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between intraretinal cystoid cavities and pre- and postoperative characteristics of eyes after closure of idiopathic macular hole

Abstract: intraretinal cystoid cavities have been detected at the edges of macular holes (MHs) but their clinical characteristics and their relationship to the MH variables have not been determined. We measured the areas of the intraretinal cystoid cavity in 111 eyes with MHs in the OCT images preoperatively. Our results showed that the intraretinal cystoid cavities were located in the Henle fiber layer-outer nuclear layer (HFL-ONL) complex in 106 eyes and in the inner nuclear layer (INL) in 89 eyes. All were resolved a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…There was a report that the closure rate of the hole could be increased if CME was treated with topical therapy in secondary FTMH [ 20 ]. Moreover, only a few studies have shown that it is associated with preoperative BCVA [ 21 ] and metamorphopsia [ 22 ]. Although the presence of IRC is assumed to have a significant effect on the morphological changes of MH, there have been no studies related to postoperative MH closure.…”
Section: Introductionmentioning
confidence: 99%
“…There was a report that the closure rate of the hole could be increased if CME was treated with topical therapy in secondary FTMH [ 20 ]. Moreover, only a few studies have shown that it is associated with preoperative BCVA [ 21 ] and metamorphopsia [ 22 ]. Although the presence of IRC is assumed to have a significant effect on the morphological changes of MH, there have been no studies related to postoperative MH closure.…”
Section: Introductionmentioning
confidence: 99%
“…Various indexes have been developed to estimate the results of these OCT measurements, including hole form factor (HFF), MH index (MHI), and tractional hole index (THI) [15][16][17][18]. At the same time, some studies have evaluated the MH area (HA) as well as the cyst areas around MH (CA) by subjecting OCT images to analysis using different software, such as Image J, which has many disadvantages [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Various indexes have been developed to estimate the results of these OCT measurements, including hole form factor (HFF), MH index (MHI), and tractional hole index (THI) [15][16][17][18]. At the same time, some studies have evaluated the MH area (HA) as well as the cyst areas around MH (CA) by subjecting OCT images to analysis using different software, such as Image J, which has many disadvantages [19,20].…”
Section: Introductionmentioning
confidence: 99%